(Analysis of Chronic Energy Deficiency (KEK) in Pregnant Women in the Sumbawa District Health Center Unit 1 Area) - Ana Lestari; Luh Putu Sri Yuliastuti; Iga Maliga; Asri Reni Handayani; Rafi’ah , Rafi’ah; Herni Hasifah; Nur Arifatus Solihah (Jurnal EduHealth, 2024)
Malnutrition, especially energy and protein in the mother Pregnancy that lasts a long time and years can cause Chronic Energy Deficiency (KEK). The aim of this research is to determine the risk factors for CED in pregnant women in the work area of the Sumbawa Unit 1 District Health Center. The method used in this research is an analytical survey with a cross sectional approach. The statistical test used was the Chi-Square test. The population in this study was all 217 pregnant women. The research sample of 46 respondents consisted of 24 respondents who experienced KEK and 24 respondents who did not experience KEK. The sampling technique uses purposive sampling. Data analysis uses univariate and bivariate. Most pregnant women who experience CED (79.2%) have less knowledge, low income (75%), lack family support (87.5%), lack support from health workers (70.8%). The results of statistical tests show that there is a significant relationship between knowledge (p=0.006), income (p=0.006), family support ( p=0.014) and support from health workers ( p=0.017) with the incidence of CED in pregnant women. There is a significant relationship between knowledge, income, family support and support from health workers with the incidence of CED in pregnant women at the Sumbawa District Health Center Unit 1